Using coherence to measure regional homogeneity of resting-state fMRI signal - Liu, Dongqiang; Yan, Chaogan; Ren, Juejing; Yao, Li; Kiviniemi, Vesa J.; Zang, Yufeng (Frontiers in Systems Neuroscience, 2010)
In this study, we applied coherence to voxel-wise measurement of regional homogeneity of resting-state functional magnetic resonance imaging (RS-fMRI) signal. We compared the current method, regional homogeneity based on coherence (Cohe-ReHo), with previously proposed method, ReHo based on Kendall’s coefficient of concordance (KCC-ReHo), in terms of correlation and paired t-test in a large sample of healthy participants. We found the two measurements differed mainly in some brain regions where physiological noise is dominant. We also compared the sensitivity of these methods in detecting difference between resting-state conditions (eyes open (EO) vs. eyes closed (EC)) and in detecting abnormal local synchronization between two groups (attention deficit hyperactivity disorder (ADHD) patients vs. normal controls). Our results indicated that Cohe-ReHo is more sensitive than KCC-ReHo to the difference between two conditions (EO vs. EC) as well as that between ADHD and normal controls. These preliminary results suggest that Cohe-ReHo is superior to KCC-ReHo. A possible reason is that coherence is not susceptible to random noise induced by phase delay among the timecourses to be measured. However, further investigation is still needed to elucidate the sensitivity and specificity of these methods.